PELATIHAN IMPLEMENTASI KAHOOT SEBAGAI MEDIA PEMBELAJARAN DALAM ERA NEW NORMAL BAGI GURU DI SD IT INSANTAMA - Anggi Andriyadi; Agus Rahardi; Lukmanulhakim; Supriyadi (Bajang Institute, 2022)
This community service aims to provide insightful knowledge to SDIT Insantama Lampung teachers about the use of Kahoot to improve teacher competence so as to help support the teaching and learning process. This service is carried out by providing training to SDIT Insantama Lampung teachers in using the Kahoot application for teachers in the teaching and learning process in the era of the covid 19 pandemic. In the era of the Covid-19 Pandemic, the implementation of service is still carried out by our team of lecturers. This activity is completed in three stages of activity, namely preparation, implementation, reporting. Preparation is carried out by conducting a preliminary survey to find out what the teachers need in classroom teaching activities. Implementation of the training, using the lecture method, namely the presentation technique, followed by direct practice assisted by the team, accompanied by questions and answers and exercises carried out by the training participants. This activity was carried out through zoom media which was due to avoid the spread of the virus and this activity was attended by approximately 20 teachers. At the reporting stage, it was made after the completion of this service activity. Based on the results of the activities that have been carried out, it can be seen that the teachers are very enthusiastic, especially when making teaching media and making exam questions